PELATIHAN PEMBERLAKUAN SISTEM AJAR JARAK JAUH (DARING) DI MIS NURUL ISLAM - Ano Maryano (SABAJAYA Jurnal Pengabdian Kepada Masyarakat, 2023)
This study aims to describe learning training and class teacher efforts in instilling noble character through religious activities in fifth grade students at Madrasah Ibtidaiyah Nurul Islam, Jatisari District, Karawang Regency. This study uses a qualitative approach which intends to understand what phenomena are experienced by research subjects. Collecting data using the method of observation, interviews, and documentation. The results showed that the efforts made by the teacher in instilling noble character in students through religious activities in class V students at Madrasah Ibtidaiyah Nurul Islam, Jatisari District, Karawang Regency were through routine activities such as carrying out Dhuha prayers in congregation, Dhuhur prayers in congregation, tahfiz juz 30 program, and muhadharah program. These routine activities are supported by the existence of facilities and infrastructure, the collaboration of the school and parents of students. The problems of these routine activities are limited time, the lack of attention from parents to the development of student character, and the influence of the surrounding environment